2013
DOI: 10.3945/ajcn.112.045377
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption in infancy and development of allergic disease up to age 12 y

Abstract: Background: Fish intake in infancy has been associated with re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 31 publications
2
53
0
1
Order By: Relevance
“…In a Norwegian birth cohort study, children who ate fish at an early age displayed a lower prevalence of allergic rhinitis at 4 years of age . The Stockholm BAMSE study found that early and regular fish consumption in infancy was associated with a reduced risk of asthma, rhinitis and eczema at 8 years of age . In addition, previous studies from our cohort have concluded that the early introduction of fish reduced the risk of eczema during the first year of life, allergic rhinitis and recurrent wheeze at 4 years of age and doctor‐diagnosed asthma at 8 years of age …”
Section: Discussionmentioning
confidence: 57%
“…In a Norwegian birth cohort study, children who ate fish at an early age displayed a lower prevalence of allergic rhinitis at 4 years of age . The Stockholm BAMSE study found that early and regular fish consumption in infancy was associated with a reduced risk of asthma, rhinitis and eczema at 8 years of age . In addition, previous studies from our cohort have concluded that the early introduction of fish reduced the risk of eczema during the first year of life, allergic rhinitis and recurrent wheeze at 4 years of age and doctor‐diagnosed asthma at 8 years of age …”
Section: Discussionmentioning
confidence: 57%
“…Anaphylaxis may also occur (Pascual et al, 2008). But according to Magnusson et al (2013), regular fish consumption in infancy may reduce the risk of allergic disease up to age of 12. Another correlation in this study was confirmed in patients with food reactions to kiwi; these patients with hypersensitivity to kiwi also have persistent eczematic lesions.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the parvalbumins, several other fish proteins, enolases, aldolases and fish gelatin seem to be important allergens . An adverse reaction to fish may be of non‐allergic origin, due to food contamination or newly formed toxic products, but the most frequent type of adverse reactions to fish are immunologic‐mediated reactions; such allergic reactions may be both IgE‐mediated and non‐IgE‐mediated . On the other hand, fish is a major source of long‐chain omega‐3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%